ANALISA TINGKAT KEPUASAN WISATAWAN TERHADAP SARANA TRANSPORTASI DALAM UPAYA MENCIPTAKAN KAWASAN WISATA TERINTEGRASI DI YOGYAKARTA (STUDI KASUS) TAMANSARI, KRATON, TITIK NOL KILOMETER DAN MALIOBORO - Sulistyo, Agung; Ayu Salindri, Yerika (Kepariwisataan: Jurnal Ilmiah, 2019)
The process of assessing the satisfaction of tourists must be done an organization or business. By knowing the attitude of tourists, Local Government can issue policies related to services for tourists and can find out how far the level of customer satisfaction with the service. Fishbein method is used to determine the attitude of tourists to a particular object or product (such as brand, service, etc.). Based on data analysis that has been done, it can be concluded that Si Thole tourism service is considered good based on tourist attitude. with attributes include: low cost, ease of access, precise purpose, quality human resources services and provide comfort for tourists. This can be seen through Fishbein analysis that has been done and obtained the mean value of 79.49. The mean values are at neutral answer intervals and agree or are on the right side indicating a positive value.Keywords: Transportation Performance Tourism, Si Thole, Fishbein Method